The Effect of Online Promotion on Purchase Interest in PT Millionaire Club Indonesia Products: Pengaruh Promosi Online Terhadap Minat Beli Pada Produk PT Millionaire Club Indonesia - Nurul Septya Magisa; Audisty Prana Hardayu (Journal of Management Specialists, 2023)
This research was conducted using descriptive analysis methods and statistical analysis methods. In the descriptive method, information was obtained from respondents through a questionnaire containing the characteristics of respondents, namely age, gender, employment status, and length of time following PT Millionaire Club Indonesia's istragram account. As for the statistical method, data processing was carried out with the SPSS 26 for Windows programme. This indicates that online promotion has a significant effect on consumer buying interest in PT Millionaire Club Indonesia products. From the data analysis, determination Test, it can be seen that R = 0.605 means that the relationship (relation) between the online promotion variable and purchase intention is 60.5%, which means it has a fairly strong relationship. R Squire is 0.366 or 36.6% of buying interest factors are influenced by online promotions. While 63.4% is influenced by things that are not researched by the author. Based on the t test, the online promotion variable has a significant positive effect on buying interest, this can be seen from the significant value of 0.000 <0.05. The value of tcount (7.518)> ttable (0.196) and by looking at the level of significance, namely the level of significance <0.05 (0.000 <0.05) then H0 is rejected and Ha is accepted, meaning that if the online promotion variable (X) is increased, buying interest (Y) will increase. The results of this test prove that consumer buying interest is influenced by online promotions. Meanwhile, if the online promotion is given negatively, it will also have a negative effect on the buying interest of PT MCI consumers in Pontianak stockists